DIRECTION FLOW (DC) ELECTRICITY PRODUCTION THROUGH THE UTILIZATION OF STONE BANANA LEATHER WASTE (MUSA BALBISIANA) TO BE AN ENVIRONMENTALLY FRIENDLY BATTERY - Rafil Arizona Rafil (UIR PRESS, 2021)
Batteries are one of the world's favorite sources of energy because of their ease and practicality of use. In a conventional battery, there are heavy metals such as mercury, lead, cadmium, and nickel. All these metals are B3 waste which is very dangerous for the environment and the human body if it is not recycled properly. Efforts that can be made to overcome the problem of B3 waste above are by researching and utilizing the waste of banana peel (Musa Balbisiana) to produce direct electrical energy (DC). With the aim of the community getting an environmentally friendly source of electrical energy, easy to recycle and worrying about the magnitude of the danger because the impact of heavy metals can be reduced. The purpose of this study is to determine the voltage (voltage) produced and the durability of the bio-battery made. The method used is to make a bio-battery paste from banana peels instead of the paste on conventional batteries. The results obtained from this study are the banana peel waste paste can conduct electricity. Produces a voltage of 1.24 volts and the bio-battery made from banana peel can last for 16 hours.